EVALUASI AKHIR DALAM IMPLEMENTASI PROGRAM GIZI ANAK SEKOLAH (PROGAS) TAHUN 2018 DI KABUPATEN KULON PROGO - Pratiwi, Siska; Syah, Justiyulfah (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
The Sustainable Development Goals (MDGs) are an international commitment to increasing development in various countries. The Indonesian government’s efforts to overcome hunger and child mortality are the implementation of the School Children’s Nutrition Program which aims to increase the balanced nutritional intake of students, improve clean and healthy living behavior and learning abilities, and increase the knowledge, attitudes, and practices of balanced nutrition for students. This study uses a qualitative method with a case study approach. Selection of informants using a purposive sampling technique. Research informants are stakeholders. Data was collected by using focus group discussions and depth interviews. Data validity is done using triangulation of sources, member checking, and peer debriefing. The results of this study found that the implementation of the Program Gizi Anak Sekolah (Progas) had stakeholders, the Progas implementation team cooperated well, parents actively assisted in preparing food (cooking), and farmers as suppliers of food ingredients, Progas also provided knowledge to children. related to nutrition. Barriers to the Program are limited human resources and limited signal in some schools. The supporting factor for Progas is good cooperation between school implementers and the surrounding community